Effectiveness of andragogical approach for homestay operators - Palal, Nor Hairul (Penerbit UTM Press, 2019)
Homestay, as a community-based tourism product of Malaysia has increased in popularity and demand among domestic and international tourists. Capacity building of homestay operators through training needs to be developed using the andragogy approach. Andragogy approach in training is chosen because of these homestay operators comprised of adults 40 years and above, and also those who do not possess any background in the tourism industry. Therefore, this study is conducted to examine the needs of the speaker approach from the perspective of the training participants. Accordingly, a qualitative study is conducted involving 50 respondents consisting of 3 groups; homestay operators, homestay coordinators and stakeholders involved with homestay in Malaysia. The usage of Atlas-Ti7 assisted in the formation of research themes and is further discussed in this study. The results show that the training needs andragogy should be applied to every course involving adults to ensure that training results are understood and applied in homestay.